(untitled) (Journal of the Bangladesh Agricultural University, 2017)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during Aman season from June to November 2016 to find out the effect of variety and planting density on weed dynamics and yield performance of transplant Aman rice. The experiment consisted of four varieties viz. Binadhan-7, BR25, BRRI dhan56 and BRRI dhan62 and four planting density viz. 25 cm × 15 cm, 25 cm × 10 cm, 20 cm × 15 cm and 20 cm × 10 cm. The experiment was laid out in a randomized complete block design with three replications. Variety exerted significant effect on weed density and dry weight at different days after transplanting (DAT). The lowest weed density and dry weight were observed in BR25 and the highest ones were observed in Binadhan-7. Weed population was not significantly affected by planting density while weed dry weight was significantly affected and closer spacing produce the lowest weed dry weight. Yield and yield contributing characters of transplant Aman rice were significantly influenced by variety and planting density. BR25 showed produce the highest plant height (157.9 cm), panicle length (24.94 cm), grains panicle(103.10), sterile spikelets panicle−1 (29.36), grain yield (4.30 t ha−1) and straw yield (8.99 t ha−1) while BRRI dhan62 the highest number of total tillers hill−1 (14.75), effective tillers hill−1 (11.62), and non-effective tillers hill−1 (3.10). The highest 1000-grain weight (25.21g) was found in the variety Binadhan-7and the highest harvest index (53.50%) was obtained from BRRI dhan56. In case of planting density, the highest value of plant height (124.27 cm), total tillers hill−1 (13.53), effective tillers hill−1 (11.20), non-effective tillers hill−1 (2.32), panicle length (22.59 cm), grain yield (4.17 t ha−1) and straw yield (5.75 t ha−1) were obtained from 25 cm × 15 cm spacing. On the other hand, the highest number of grains panicle−1 (84.23) and harvest index (45.18 %) were obtained from 25 cm × 10 cm spacing, heaviest 1000-grain weight (23.83 g) from 20 cm × 15 cm spacing. Experimental results indicated that BR25 grown under 25 cm × 15 cm planting density appeared to be the best in order to get maximum grain yield as well as reducing weed infestation. J. Bangladesh Agril. Univ. 15(2): 167-173, December 2017